Draft Annual Plan 1982-83 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1982)
From the above it can be seen that the season continuing to be favourable and with an anticipated good Rabi the targets set for the year 1981-82 can be realised. The satisfactory inputs position supported by adequate credit operations is expected to give significant results to realise the targets. In view of the National priority accorded to Oilseeds and Pulses to over come shortages, adequate emphasis is laid on improvement of productivity and production of these crops.
Government of Andhra Pradesh, Finance and Planning (Planning Wing) Department